EXAMINING URBAN AND RURAL PHARMACY AVAILABILITY IN MINNESOTA FROM 2009 TO 2020 - Katy Lehenbauer, MD, MPH (Elsevier, 2024)
Therapeutic Area: ASCVD/CVD in Special Populations Background: Cardiovascular disease (CVD) is the leading cause of death in the United States. Controlling CVD risk factors is key to treatment and prevention. However, medication adherence is difficult when pharmacies are difficult to access. This study aims to characterize pharmacy access by geographic region in Minnesota from 2009 to 2020. Methods: Pharmacy lists for 2009 and 2020 were obtained from the Minnesota Board of Pharmacy. Pharmacies were geocoded and labeled with a rural-urban community area (RUCA) code. Geographic areas were divided into 3 RUCA areas: urban, large rural city/town, small/isolated rural town. Each pharmacy was designated as a chain, supermarket-based, independent, or associated with a health system. We evaluated pharmacy hours, count and density for each geographic area by year, and the proportion of pharmacy types in all geographic locations. Results: A total of 1,010 pharmacies were open in 2009 and 916 pharmacies in 2020. Pharmacy density (n/100,000 resident) decreased over time for all geographic areas: urban from 17.0 to 13.9, large rural from 24.1 to 21.1, and small rural from 25.6 to 24.2. Pharmacy types also changed over time. While chain pharmacies accounted for nearly half of pharmacies in both 2009 and 2020, independent pharmacies decreased over time in all regions (Figure 1). Supermarket and health system pharmacies represented a stable or increasing share of all pharmacies although the absolute number of pharmacies decreased everywhere except in small rural towns.Supermarket pharmacies had the best access; >95% were open after 6pm and had open hours on the weekend. Chain pharmacies had similarly high accessibility in the urban regions, but were less accessible in large rural city (65% extended hours, 87% open weekends) and small town (23% extended hours, 66% open weekends) regions (Table 1). Independent pharmacies tended to be open on weekends, but were less likely to have extended hours. Conclusions: Pharmacy access decreased across the state of Minnesota from 2009 to 2020, especially for independent pharmacies. Residents of less populated areas had fewer options for pharmacy use outside of regular business hours.